Detection of Mycoplasma spp., herpesviruses, topiviruses, and ferlaviruses in samples from chelonians in Europe. (November 2017) - Kolesnik, Ekaterina; Obiegala, Anna; Marschang, Rachel E.
We tested samples from 1, 015 chelonians in Europe for Mycoplasma spp., herpesviruses, ranaviruses, picornaviruses, and ferlaviruses by PCR. Mycoplasma spp. were detected in 42.1% and herpesviruses were detected in 8.0% of tested chelonians. Differentiation of the herpesviruses revealed that 46.9% of the detected chelonian viruses were testudinid herpesvirus 1 (TeHV-1) and 54.3% were TeHV-3, including co-detections of TeHV-1 and -3 in 3 tortoises. TeHV-4 was detected in a leopard tortoise ( Stigmochelys pardalis ), and a herpesvirus that could not be further characterized was found in a pond slider ( Trachemys scripta ). Picornaviruses (topiviruses) were detected in 2.2% of the tested animals; ferlaviruses were found in 0.6%; no ranaviruses were detected in any of the animals tested. Mycoplasma spp. were detected significantly more often in Horsfield's tortoises ( Testudo horsfieldii ), leopard tortoises, and Indian star tortoises ( Geochelone elegans ) than in other species. Horsfield's tortoises were also significantly more often positive for TeHV-1. Mycoplasma and TeHV-1 were co-detected in 3.0%, and mycoplasma and TeHV-3 in 2.3%. The TeHV-4–positive tortoise was also positive for mycoplasma. Mycoplasma and picornaviruses were co-detected in 1.2% of the tortoises. A spur-thighed tortoise ( Testudo graeca ) was positive for mycoplasma and a ferlavirus. In some cases, >2 pathogens were detected. A significant correlation between mycoplasma and herpesvirus detection was found. Of all tested animals, 47.6% were positive for at least one pathogen, demonstrating the importance of pathogen detection in captive chelonians.